The Role of Prosecutors in The Effort For Assets Recovery From Corruption Crimes - Midian Hosiholan Rumahorbo; Risa Mahdewi; Desia Rakhma Banjarani (Ius Poenale, 2022)
Corruption is an extraordinary crime because the impact of corruption harms the financial condition of a country; corruption is also alleged to violate the social and economic rights of the community or citizens in the country. Since corruption criminal is included as a extraordinary crime, an extraordinary method must be applied to eradicate corruption. For this reason, also steps are needed to provide a deterrent effect to perpetrators of corruption. Punishment of corruption perpetrators is expected to provide a deterrent effect. One of that steps is to return the state losses caused by corruption perpetrators, as well as being one of the anticipatory steps so that later, people will not dare to commit corruption. This research was made to answer how to recover assets from corruption and determine the prosecutor's office's role in recovering assets from corruption crimes. In this research, the author uses a normative legal research method that conducts an inventory of applicable laws and regulations. The results of research regarding efforts to recover assets can be carried out through criminal and civil legal remedies. Furthermore, the role of the Prosecutor's Office as a law enforcement officer in charge of law enforcement regarding assets recovery through criminal acts recognizes two mechanisms or procedures for recovery assets, the first mechanism or procedure is the seizure of assets without punishment, and the second is the mechanism or procedure for voluntary asset return. The steps that can be carried out in asset recovery are divided into several steps, including asset tracking, blocking or freezing, foreclosure, confiscation, and return.